Qualitative Research and Its Place in Health Research in Nepal - van Teijlingen, E; Simkhada, B; Porter, M; Simkhada, P; Pitchforth, E; Bhatta, P (Kathmandu University Medical Journal, 2012)
There has been a steady growth in recent decades in Nepal in health and health services research, much of it based on quantitative research methods. Over the same period international medical journals such as The Lancet, the British Medical Journal (BMJ), The Journal of the American Medical Association (JAMA) and the Journal of Family Planning & Reproductive Health Care and many more have published methods papers outlining and promoting qualitative methods. This paper argues in favour of more high-quality qualitative research in Nepal, either on its own or as part of a mixed-methods approach, to help strengthen the country’s research capacity. After outlining the reasons for using qualitative methods, we discuss the strengths and weaknesses of the three main approaches: (a) observation; (b) in-depth interviews; and (c) focus groups. We also discuss issues around sampling, analysis, presentation of findings, reflexivity of the qualitative researcher and theory building, and highlight some misconceptions about qualitative research and mistakes commonly made. DOI: http://dx.doi.org/10.3126/kumj.v9i4.6350 Kathmandu Univ Med J 2011;9(4):301-5